The attitude of master students to Blended Learning - Калиаскарова, Айнур; Жундыбаева, Турархан (Pedagogy and Psychology, 2022)
The topic of blended learning in Kazakhstan is very relevant and in demand today. Despite this, there are still no studies that would demonstrate the attitude of master students towards blended learning. In this regard, this study will be especially relevant. The purpose of the study is to study the problem of blended learning, to determine the attitude of master students to blended learning. Objectives of the work: to define the concept of blended learning, to identify the problem of a blended learning format in foreign and local institutions, to determine the attitude of master students in Kazakhstan to blended learning. To achieve the goal, the authors conducted a survey among undergraduate students. The survey was conducted online using a Google Form. 76 undergraduates became its participants, and according to the results of the survey, the majority of undergraduates are familiar with blended learning, know it and support this learning format. Since blended learning includes both online and traditional learning, it was even determined which part the undergraduates prefer. Almost everyone chose the online part of their studies, as it saves travel time and also encourages self-study. Both the advantages and disadvantages of blended learning are in its online part of learning, while the disadvantage of offline learning is only the time spent on the road. In general, all undergraduates recognize the blended learning format as successful and offer to teach all subjects in this format in the future.